2019
DOI: 10.18087/cardio.2019.5.2607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Myocardial Reperfusion on Ischemic Mitral Regurgitation in Patients with Acute Myocardial Infarction

Abstract: Background. During the restoration of blood flow in the ischemic area of the myocardium, viable cardiomyocytes are damaged over a few minutes of tissue reperfusion (reperfusion myocardial damage). It is known that ischemic mitral regurgitation (IMR) develops in 11–19 % of patients who have undergoing percutaneous coronary intervention (PCI) in symptomatic coronary heart disease (CHD). To present day, the influence of myocardial reperfusion on IMR in patients with acute myocardial infarction (AMI) is not fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Atorvastatin is a statin lipid-regulating drug (26), mainly acting on the liver, which can reduce the synthesis of cholesterol and has the effect of lowering blood lipid (27,28). Statins lipid-lowering drugs can improve the cardiac function of patients with acute myocardial infarction (29), and can be used for the treatment of the disorder of lipid metabolism in patients caused by acute myocardial infarction, which is beneficial to the treatment of acute myocardial infarction. Ielasi et al (30) found that atorvastatin combined with aspirin has a synergistic effect in the treatment of ischemic stroke, which can be a testament to our experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…Atorvastatin is a statin lipid-regulating drug (26), mainly acting on the liver, which can reduce the synthesis of cholesterol and has the effect of lowering blood lipid (27,28). Statins lipid-lowering drugs can improve the cardiac function of patients with acute myocardial infarction (29), and can be used for the treatment of the disorder of lipid metabolism in patients caused by acute myocardial infarction, which is beneficial to the treatment of acute myocardial infarction. Ielasi et al (30) found that atorvastatin combined with aspirin has a synergistic effect in the treatment of ischemic stroke, which can be a testament to our experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…Trial sequential analysis was performed using TSA software (version 0.9.5.9 Beta; Copenhagen Trial Unit, Copenhagen, Denmark), The Lan–DeMets approach was used for construction of the O'Brien‐Fleming monitoring boundaries and the optimal information size, which was set to an alpha of 0.05 with a two‐sided beta of 0.80 and relative risk reduction of 10%. The mortality incidence in the control group was set according to previously published studies 11–17 …”
Section: Discussionmentioning
confidence: 99%
“…Mortality data were available from all seven included studies with various follow‐up durations 11–17 . In the study by Hofmann and colleagues, the duration of patient follow‐up was 1 year, which was the longest.…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations